How do Financial Intermediaries Create Value in Security Issues? - Adriani, Fabrizio; Deidda, Luca G.; Sonderegger, Silvia (Review of Finance, 2014)
Abstract We study incentive provision in a model of securities issuance with an informed issuer and uninformed investors. We show that the presence of an informed intermediary may increase surplus even if we allow for collusion between the intermediary and the issuer. Collusion is neutralized by introducing a misalignment between the interests of the issuer and those of the intermediary. To achieve this, the intermediary commits to hold some of the securities. The intermediary then underprices the remaining securities and extracts any investor surplus through a “participation fee.” We provide an explanation for the diffusion of book building and quid pro quo practices in Initial Public Offerings (IPOs).